Stress symptoms due to psychological pressure in paramedical workers: study in public health organization of Ain Berda – Annaba - Belhay, Hassina (Journal of Human Sciences, 2023)
People suffers from psychological pressure and troubles are always in destabilized status, which is reflected in their behavior as well as psychological status. This trouble is seen through a permanent anxiety (stress), which can be noticeable in a variety of symptoms.This study will shed light on these symptoms through a study on group of paramedical workers in a public health organization.